Nutritional Variation in Fruits and Seeds of Pumpkins (Cucurbita Spp) Accessions from Nigeria - Nwofia, G.E.; Victoria, N. Nwogu; Blessing, K. Nwofia (Pakistan Journal of Nutrition, 2012)
Fruits and seeds of Nineteen accessions of Cucurbita collected from three agro ecological zones of Nigeria were evaluated for their physical attributes, proximate values, minerals, vitamins and anti-nutritional factors. The result indicated that there was significant differences in the accessions for moisture content, crude fibre, ash, crude protein, fat and carbohydrate in the fruits (p<0.01) while crude fibre and carbohydrate was not significant in the seeds (p>0.05). The moisture content ranged from 78.46 to 91.97% in the fruits while in the seeds, it ranged from 44.73 to 53.04%. The ash, crude fat and crude protein content was generally higher in the seeds than the fruit pulp indicating that the seeds are high in essential nutrients. The Nigerian accessions of Cucurbita species have low levels of tannin, flavonoids, phenols and alkaloids but the hydrogen cyanide was high. The vitamin C content was high among the fruits and seeds while thiamine and riboflavin content was moderate. The variations observed among the accessions can be explained with the first four principal component axis which accounted for 84.5% of the total variations observed with crude fibre, moisture and crude protein being the most important contributing variables. Genetic component analysis showed that most of the traits had more genetic than non-genetic factors contributing to the variability which indicates that selection can be effective in the improvement of these traits. This was further validated by such traits such as ash, niacin, flavonoids and alkaloids having high heritability and high genetic advance which means that they can be improved by selection directly.